2020
DOI: 10.1177/0023830920947769
|View full text |Cite
|
Sign up to set email alerts
|

The Reliability of Individual Differences in VOT Imitation

Abstract: Recent work has shown that individuals vary in phonetic behaviors in ways that deviate from group norms and are not attributable to sociolinguistically relevant dimensions such as gender or social class. However, it is unknown whether these individual differences observed in the lab are stable characteristics of individuals or whether they simply reflect noise or sporadic fluctuations. This study investigates the individual-level stability in imitation of a model talker’s artificially-lengthened VOT. We use a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 47 publications
2
8
0
Order By: Relevance
“…In spite of the theoretical value of capturing such tendencies in pronunciation data, that emphasis appears to be at odds both with common anecdotal reports and with longitudinal data (Munro et al, 2015) indicating large inter-learner differences in pronunciation learning trajectories. Recent work by Wade et al (2020) illustrates how an excessive focus on group means "masks the complexity of phonetic behaviors." Their native English VOT data showed that individual departures from group performance were often stable, indicating that between-speaker variability was not simply "noise, " but reflected systematic individual differences from group norms that were not explicable on linguistic or sociolinguistic grounds.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the theoretical value of capturing such tendencies in pronunciation data, that emphasis appears to be at odds both with common anecdotal reports and with longitudinal data (Munro et al, 2015) indicating large inter-learner differences in pronunciation learning trajectories. Recent work by Wade et al (2020) illustrates how an excessive focus on group means "masks the complexity of phonetic behaviors." Their native English VOT data showed that individual departures from group performance were often stable, indicating that between-speaker variability was not simply "noise, " but reflected systematic individual differences from group norms that were not explicable on linguistic or sociolinguistic grounds.…”
Section: Introductionmentioning
confidence: 99%
“…However, few convergence studies include retesting to demonstrate that individuals are consistent in these differences, and the size of the effect is often small. There is some evidence for individual tendencies in convergence within a given linguistic characteristic between instances of same task or similar tasks (Sanker, 2015; Wade et al, n.d.), but evidence for tendencies across different tasks is weaker (Pardo et al, 2018). The results of our study, in which each individual conversed with several different interlocutors on different topics, provide little evidence for individual tendencies in convergence.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that individual differences in convergence by speaker and by interlocutor, if they exist, are too weak to be reliably detected by the method used here. Recent work has generally also found a lack of consistency in the degree of convergence exhibited by individual speakers across tasks (Pardo et al, 2018) or in different conversations (Cohen Priva & Sanker, 2018), though they exhibit some consistency within a linguistic characteristic in the same task (e.g., Wade et al, n.d.). Pardo et al (2017) found that some model talkers consistently elicited more convergence than others in the same shadowing task with the same recordings.…”
Section: Methods Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…A multitude of factors, including bilingualism (Spinu et al, 2020), musical experience (Coumel et al, 2019), and general cognitive processes (working memory: Reiterer et al, 2011; neurocognitive flexibility: Reiterer et al, 2013) have been shown to correlate with individuals' extent of imitation. The list of social or personality-related factors proposed to condition imitation expands even further when considering the better-studied domain of phonetic convergence (see Wade et al, 2020 for a review). While intriguing, findings can be inconsistent and often fail to replicate across studies, making it difficult to draw firm conclusions about the individual characteristics governing imitation (Cohen Priva & Sanker, 2020;Wade, 2022).…”
Section: Predictors Of Variability In Imitationmentioning
confidence: 99%